Modeling and Experimental Assessment of the EMI Characteristics of Switching Converters With Power Semiconductor Filters - Fan, John Wing-To; Chow, Jeff Po-Wa; Chan, Wan-Tim; Zhang, Kun; Relekar, Akhil; Ho, Ka-Wai; Tung, Chung-Pui; Wang, Ke-Wei; Chung, Henry Shu-Hung (IEEE transactions on power electronics, 2020)
An input filtering technology named "power semiconductor filter (PSF)" has been proposed recently. Its operating principle is based on using a series pass device (SPD) to profile the wave shape and magnitude of the input current of converters. The voltage across the SPD is regulated around the "knee point" of the current-voltage characteristic of the SPD to minimize the power dissipation of the SPD. This paper reports the conducted electromagnetic interference (EMI) performance of the converters with the PSF. To suppress differential-mode (DM) EMI, a fast current regulation circuit is proposed to tightly regulate the current through the SPD. To suppress common-mode (CM) EMI, a single CM noise bypass capacitor is proposed. Detailed mathematical models for describing the frequency response of the SPD and main components in the driving network are formulated. A set of selection guidelines for the components will be given. The derived models will be validated by comparing the theoretical prediction with the measurement results of a 100 W, 90-264 Vac LED driver using a buck-boost converter. Results reveal that the PSF reduces the DM noise level by 47.47 dBμV. The CM noise level is reduced by 21.4 dBμV with the bypass capacitor. An integrated circuit for the controller is illustrated to demonstrate the feasibility of reducing the form factor of the filtering section.